The analysis of semiotic signs appearing on the names of Acehnese online newspapers - Fitria Arafah; Dohra Fitrisia; Siti Sarah Fitriani; Fathimath Shaheema (Studies in English Language and Education, 2023)
This study was carried out to analyze semiotic signs appearing on the names of Acehnese online newspapers. The method used in this research was qualitative by using content analysis, and the technique used for this research was documentation. The instrument used to collect the data for this research was a checklist by reviewing the names of Acehnese online newspapers: Aceh Redaksi, Kabar Aceh, Aceh TerUpdate, Aceh Info, Aceh WorldTime, and Acehzone_id. The data was analyzed using the sign theory of icons, indices, and symbols. The result of the analysis found that the signs which appeared on the names of Acehnese online newspapers and the meaning which appeared on them were related to the history of Aceh. They have the same characteristics in the use of colors: red, white, and black. These are the hues used on Aceh’s flag, which serves to represent the identity of the Acehnese. Since the newspaper organizations were also part of the Aceh community, Acehnese online newspapers also had the same culture. Thus, using the flag colors strengthened their identity and signified their origin. White is a symbol of purity, honesty, and kindness, meanwhile black refers to a warning and grief to the heroes, and finally, red symbolizes courage and heroism. The representation of the flag and people, in general, revealed the Acehnese desire to have a distinct identity from other Indonesian ethnicities in the 38 provinces of this country. Such portrayal was designed to create a distinct identity within the diversity of Indonesia.